Suicide Death from Paraquat Auto-Inoculation: A Case Report (Medico Legal Update, 2019)
We examine a case involving a 34-year-old man who died of complications following the self-inoculationof Paraquat for suicidal purposes. During the crime scene investigation were seized all the paraphernaliawere analyzed and were positive for Paraquat. At the autopsy were found an area of hemorrhagic infiltrationon the inside face of the abdominal wall, in correspondence of the right peri-umbilical region, followingthe self-inoculation of the Paraquat performed. The aspects of greatest interest of the particular case underexamination have been analyzed. In particular, we have taken into consideration the biochemical andtoxicological aspects of Paraquat and the medico-legal problems related to the inoculation of the compound.